The Influence of Work Motivation on Employee Performance at PT. Genta Trikarya Sumedang - Nur'arif, Muhammad Irfan; Supriatna, Endang; Achirnawati, Putri (Journal of Bussines Management Basic, 2024)
This study entitled the effect of work motivation on employee performance at PT. Genta Trikarya Sumedang. The problem of this research is the lack of optimal facilitation of improving employee performance. The purpose of the study was to determine work motivation, employee performance, the magnitude of the influence of work motivation on employee performance at PT. Genta Trikarya Sumedang. This study uses a descriptive research method approach with quantitative analysis techniques, conducted through a survey method. Data collection techniques were analyzed by means of observation and questionnaires. The population is the performance of employees at PT. Genta Trikarya Sumedang as many as 50 people and the research sample was 50 people. The research data uses simple regression analysis, correlation test, coefficient of determination and hypothesis testing. The results of this study indicate that work motivation is 1,915 (good enough) with an average of 63.73%, employee performance is 1,617 (good enough) with an average of 64.76%, then the magnitude of the relationship between work motivation and employee performance at PT. Genta Trikarya Sumedang of 0.820 (very strong relationship), and the magnitude of the influence of work motivation on employee performance at PT. Genta Trikarya Sumedang amounted to 67.2% and there are still 32.8% of other factors. The results of the calculation of the hypothesis test, it turns out that tcount (9.93) > ttable (1.67722), it can be said that there is a positive influence between Work Motivation on Employee Performance at PT. Genta Trikarya Sumedang is acceptable. To increase work motivation can be useful because it is human nature that requires some kind of inducement, encouragement or incentive to get better performance. Motivation acts as a technique to improve the performance of employees working at different levels.